Immune cell infiltration landscapes in pediatric acute myocarditis analyzed by CIBERSORT. Issue 2 (February 2021) - Kawada, Jun-ichi; Takeuchi, Suguru; Imai, Hiroshi; Okumura, Toshihiko; Horiba, Kazuhiro; Suzuki, Takako; Torii, Yuka; Yasuda, Kazushi; Imanaka-Yoshida, Kyoko; Ito, Yoshinori
Highlights: Endomyocardial biopsy samples of acute myocarditis were analyzed by CIBERSORT. Activated NK cells were the most prevalent population in two cases. Activated memory CD4+ and M2 macrophages were the most prevalent in one case each. Overall CIBERSORT results were consistent with those of immunohistochemistry. CIBERSORT is a promising tool to analyze immune cell landscapes in myocarditis. Abstract: Background: Myocarditis is an inflammatory disease of the myocardium, which leads to cardiac dysfunction and heart failure. Previous studies have suggested that complex cross-talk between innate and adaptive immune responses is involved in the pathogenesis of acute myocarditis. Immunohistochemistry is the current standard method for the evaluation of infiltrating immune cells, however, it is difficult to investigate and quantify many immune cell populations using this technique. Methods: Endomyocardial biopsy samples of five pediatric patients with myocarditis were analyzed by cell-type identification by estimating relative subsets of RNA transcript (CIBERSORT), a computational method for quantifying cell fractions from tissue gene expression profiles. CIBERSORT results were then compared with immunohistochemistry analyses. Results: Significant results of immune infiltrate deconvolution were obtained in four patients with fulminant myocarditis by CIBERSORT analysis. Among 22 immune cell types, 19 cell types were detected in one or more patients. Activated NK cells were the most prevalent population in two patients, whereas activated memory CD4 + T cells and M2 macrophages were the most prevalent population in one patient each. Overall CIBERSORT results were consistent with those of immunohistochemistry, although some discrepancies were observed. Conclusions: Infiltrating immune cell subsets detected by CIBERSORT analysis can reflect the time course of innate and adaptive immune responses in acute myocarditis. CIBERSORT may have the potential to characterize the detail of infiltrating immune cells in myocardial tissues and provide novel insights into the pathogenesis of acute myocarditis.